Explanation:
To solve a system of equations by substitution, you can solve one of the equations for one of the variables and substitute this expression into the other equation. This will give you an equation with only one variable, which you can then solve to find the value of that variable. You can then substitute this value back into one of the original equations to find the value of the other variable.
In this case, the given system of equations is:
y = -4
y = -2x - 20
Since the second equation is already in the form y = ..., we can substitute the expression for y from the second equation into the first equation:
-4 = -2x - 20
Solving this equation for x, we get:
x = -12
Substituting this value of x back into the second equation, we get:
y = -2(-12) - 20
= 24 - 20
= 4
Therefore, the solution to the system of equations is (x, y) = (-12, 4).